2015
DOI: 10.1158/1055-9965.epi-14-1076
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Age and Race and the Risk of Large Bowel Polyps

Abstract: Background Blacks have a higher incidence of colorectal cancer (CRC) and a younger age at diagnosis compared to Whites. Few studies have investigated racial differences in risk of metachronous adenomas and serrated polyps whether this risk differs by polyp characteristics or age of patient. Methods We analyzed data pooled from three placebo-controlled adenoma chemoprevention trials to explore racial differences in the risk of large bowel polyps in patients ≤50 and > 50 years of age. Using generalized linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For advanced neoplasia, much of the difference was driven by the higher prevalence of advanced serrated lesions in White individuals (Supplementary Table 1), which is consistent with previous studies. 18,19 However, studies have shown that the prevalence of the CpG island methylator phenotype-the CRC molecular pathway associated with serrated lesions-is lower in EOCRC than in late-onset CRC, suggesting serrated lesions are not the primary reason for the rise in EOCRC. 20 Indeed, when serrated lesions were excluded and the outcome was restricted to advanced adenomas and CRC, White individuals still had slightly higher prevalence in those younger than 60 years, whereas Black individuals had higher prevalence than White individuals in older age groups (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For advanced neoplasia, much of the difference was driven by the higher prevalence of advanced serrated lesions in White individuals (Supplementary Table 1), which is consistent with previous studies. 18,19 However, studies have shown that the prevalence of the CpG island methylator phenotype-the CRC molecular pathway associated with serrated lesions-is lower in EOCRC than in late-onset CRC, suggesting serrated lesions are not the primary reason for the rise in EOCRC. 20 Indeed, when serrated lesions were excluded and the outcome was restricted to advanced adenomas and CRC, White individuals still had slightly higher prevalence in those younger than 60 years, whereas Black individuals had higher prevalence than White individuals in older age groups (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Silber et al found an absolute difference of 9.9% in 5-year survival between African American and Caucasian patients [ 27 ]. Wallace et al demonstrated a higher risk of metachronous adenomas in African Americans compared with whites at younger ages [ 28 ]. There was a lack of data for direct comparisons in terms of CRC survival for Caucasians and Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with a previous study that demonstrated at a follow-up of 38 months, recurrent adenomas were detected in 34% and an advanced adenoma in 7% of patients under the age of 50. 8 Kim et al 6 from Korea likewise compared the risk of metachronous advanced neoplasia in a cohort of 3058 subjects aged 20 to 49 versus an older group of 1125 subjects aged 50 to 54 years at time of baseline colonoscopy. They found no significant difference in metachronous advanced neoplasia between the 2 groups among all 3 baseline risk categories (high-risk adenoma, low-risk adenoma, and no neoplasia).…”
mentioning
confidence: 99%